Numerical Optimization of a Pseudoparabolic Systems with Memory - Anikushyn, Andrii; Nazarchuk, Viktoria (Modeling, Control and Information Technologies: Proceedings of International scientific and practical conference, 2025)
We employ the method of a priori inequalities in negative norms to prove the existence of a pointwise optimal control for the regularized problem corresponding to a time-nonlocal pseudoparabolic integro-differential equation with a Volterra-type integral term. Certain differential properties of the cost functional are investigated, and a numerical example illustrating the computation of the optimal control is presented.